Necrobiosis lipoidica - an old but challenging dermatosis - Magdalena Ciążyńska; Igor Bednarski; Joanna Narbutt; Anna Woźniacka; Aleksandra Lesiak (Termedia Publishing House, 2016)
Introduction . Necrobiosis lipoidica (NL) is a rare skin condition associated with diabetes that occurs in 0.3-1% of diabetic patients. Nevertheless, there are patients who develop this entity in the absence of diabetes mellitus. Objective. To highlight some problems in differential diagnosis and treatment of NL. Case report . We report a case of a 44-year-old woman with a 3-year history of undiagnosed skin lesions. Clinical examination revealed atrophic plaques on an erythemal background located on both shins. The first histopathological examination revealed infiltrated granulomatous lesions, later confirmed as deep tuberculoides chronic granulomatous dermatitis. However, after 6-month anti-tubercular treatment skin lesions were still present. Based on another skin biopsy we restricted the diagnosis to polyarteritis nodosa, necrobiosis lipoidica and granuloma annulare. Further examination led us to establish a diagnosis of necrobiosis lipoidica. The patient was treated with many therapeutic regimens without a satisfactory response. Conclusions . Lack of treatment guidelines and therapy based on dermatologists' clinical experience suggest that NL needs to be evaluated in the near future. A large retrospective study and systematic review are required to establish diagnostic and treatment regimens.